PLEASE (Pick, List, Evaluate, Activate, Supply, and End) Strategy Toward Student’s Writing Achievement on Recount Text - Ni’matul Farikhah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2019)
The thesis entitled “The Influence of Using PLEASE (Pick, List, Evaluate, Activate, Supply And End) Strategy Toward Student’s Writing Achievement on Recount Text at The Tenth Grade of SMA Pangudi Luhur Sukaraja”. The problem of this study as follows “Is there any significant differences between the students who are taught by using the PLEASE strategy and who are not taught by using the PLEASE strategy toward student’s writing achievement on recount text at the tenth grade of SMA Pangudi Luhur Sukaraja?”. In this study, the writer used a quasi-experimental design. The population in this study was the tenth-grade students of SMA Pangudi Luhur Sukaraja, with the total of the population was 64 students. Whereas, the sample of the study was 40 students were taken by using purposive sampling, those were 20 students of X IPS1 as experimental group and 20 students of X IPS2 as the control group. Moreover, the writer used a written test. The data obtained from Independent t-test analysis, between the result of the post-test in experimental class and control class. Based on the calculation by using an Independent t-test, the researcher found that tobtained was higher than ttable (6.211> 1.697) at the significance level ɑ = 0.05 in a two-tailed test. So, the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (Ha) was accepted. It can be concluded that there was any significant difference in teaching writing by using PLEASE Strategy in SMA Pangudi Luhur.